COMPARATIVE ANALYSIS OF DIGITAL SIGNATURE ALGORITHMS (RSA, ELGAMAL) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper deals with one of the most important tasks of cryptography - the electronic digital signature. Electronic digital signature (EDS) is needed to uniquely establish the author of any document. EDS is the analog of a common signature that authenticates any document or contract. In this paper we look at the advantages and disadvantages of the algorithms RSA, ElGamal.